Brief Note on System Signature and Long Term Method - Gurcan, Mehmet; Bugatekin, Ayse T. (E D P Sciences, 2018)
In this paper, the system signature of the system is creating by using the long-term method and then the transition matrices of each step are calculated. In this way, it is possible to have information about the reliability of the system after each unit becomes failure. Also, in this study, three systems are presented as examples.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS